Pronounced Differences of Recombination Activity at the Sex Determination Locus of the Honeybee, a Locus Under Strong Balancing Selection - Hasselmann, Martin (Copyright © 2006 by the Genetics Society of America, 2006)
Recombination decreases the association of linked nucleotide sites and can influence levels of polymorphism in natural populations. When coupled with selection, recombination may relax potential conflict among linked genes, a concept that has played a central role in research on the evolution of recombination. The sex determination locus (SDL) of the honeybee is an informative example for exploring the combined forces of recombination, selection, and linkage on sequence evolution. Balancing selection at SDL is very strong and homozygous individuals at SDL are eliminated by worker bees. The recombination rate is increased up to four times that of the genomewide average in the region surrounding SDL. Analysis of nucleotide diversity (π) reveals a sevenfold increase of polymorphism within the sex determination gene complementary sex determiner (csd) that rapidly declines within 45 kb to levels of genomewide estimates. Although no recombination was observed within SDL, which contains csd, analyses of heterogeneity, shared polymorphic sites, and linkage disequilibrium (LD) show that recombination has contributed to the evolution of the 5′ part of some csd sequences. Gene conversion, however, has not obviously contributed to the evolution of csd sequences. The local control of recombination appears to be related to SDL function and mode of selection. The homogenizing force of recombination is reduced within SDL, which preserves allelic differences and specificity, while the increase of recombination activity around SDL relaxes conflict between SDL and linked genes.